Relationship Between Certain Biochemical Parameters and Maximal Aerobic Speed of Elite Soccer Players - Cebi, Mehmet; Ceviker, Abdulkerim; Ozlu, Kurtulus; Elioz, Murat; Yamak, Bade; Kusan, Osman; Agaoglu, Seydi Ahmet; Dogan, Erol; Ceylan, Levent (Progress in Nutrition, 2021)
Study Objectives: In this study, it was aimed to evaluate the relationship between vitamin D and lipid profiles of athletes playing football professionally during the season and some metabolic parameters and maximal rate. Methods: 52 male elite soccer players performing in Super League, TFF 2nd League, and TFF 3rd League whose mean age 22.86±3.55 years, participated in our study. The sport age of the soccer players was 12.2±1.70 years. The participants attended in at least five 80-minute training periods and performed at least one official competition weekly (through 11 months). In November, blood samplings of the athletes and other parameters were obtained between 09:00 and 10:00 a. m. leading a 12-hour fasting period. The Maximal Aerobic Speed ​​(MAS) measurement developed by Buchheit (2008) to evaluate aerobic power and capacity was used to carry out the study. In order to determine the relationship between the variables of individuals, Pearson Correlation Test was used as the data showed normal distribution. Results: Albumin, Alp, Alt, Ast, B12 vitamin, Ca, Phosphorus, Creatinine, Mg, Free T3, Sodium, Tsh, Ferritin, Folic Acid, Potassium Triglyceride, Glucose, Total Cholesterol, and Free T4 values were found within normal limits. It can be said that athletes had low vitamin D values. It was observed that the participants had low LDL cholesterol values. Variables don’t have any significant effects on running time, peak velocity, true vift and VO2max of biochemical parameters (p>0,05). Conclusion: As a result, it can be concluded that despite the positive relationship between the maximal aerobic velocity test parameters of the footballers and their pre-test biochemical results, it wasn’t statistically a meaningful relationship.